Inclusão e formação docente : histórias de vida de professores da rede pública municipal de Maceió - Barros, Márcia Lúcia Nogueira de Lima (2009)
The life's history is permeated by a set of meanings that intertwine personal life at work. The teacher's work is influenced by subjective - cultural and ideological - factors. Considering the importance of tracking the life's history for professional performance, this study aimed to examine aspects (family, school and professional) of primary teachers' life's history and their involvement on the inclusion process of students with disabilities. To this end, I chose a qualitative research, having as methodological approach the life's history. The participants were nine (09) elementary school teachers of municipal schools in Maceió-AL. The resources used for data collection were the narrative interview and the field diary. The research corpus was constructed from three generative questions: Are teachers who had contact with people with disabilities more involved with the inclusion process? Do Teachers who have family members with disabilities perceive themselves more committed to the inclusion process than other professionals? What makes teachers have an inclusive practice while many reject the student with disabilities? The theoretical study is based principally on Schon (2000), Mantoan (2003), Nóvoa (2000), Josso (2002) and Moita (2000), among others. Were established as analysis categories emerged from the interviews: 1) Contact with people who had disabilities (family / school), 2) the relationship between Life's History and career choice, 3) challenge with the students with disabilities inclusion 4) self-education as a continuous education process and 5) Relationship between life's history and practice of the teacher. From the data analysis, I found that teachers demonstrated similar goals in their speech, as the redeem of values and principles that are important in educational work and that the recollection of some experiences interact with a theoretical and reflective base, contributing effectively in the educational process in which they live, also including the possibilities to change and innovate their practice. As a result, the investigation revealed that the integration of knowledge related to family life, school and training were paramount for them to succeed in their teacher training.